2007
DOI: 10.1113/jphysiol.2006.122432
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 regulates Ca2+ entry via arachidonate‐regulated Ca2+‐selective (ARC) channels without store depletion or translocation to the plasma membrane

Abstract: Recent studies have indicated a critical role for STIM (stromal interacting molecule) proteins in the regulation of the store-operated mode of receptor-activated Ca 2+ entry. Current models emphasize the role of STIM located in the endoplasmic reticulum membrane, where a Ca 2+ -binding EF-hand domain within the N-terminal of the protein lies within the lumen and is thought to represent the sensor for the depletion of intracellular Ca 2+ stores. Dissociation of Ca 2+from this domain induces the aggregation of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
224
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(248 citation statements)
references
References 35 publications
20
224
1
3
Order By: Relevance
“…In addition, impairment of this complex by shTRPC3 was without effect on TG-evoked SOCE. The role of STIM1 in non-capacitative receptor-regulated Ca 2ϩ entry pathways, such as Ca 2ϩ entry via arachidonate-regulated calcium (ARC) channels (59,60) has previously been demonstrated. Our results reporting the association of STIM1 with type I IP 3 R upon stimulation with ATP or CCh also shows the involvement of STIM1 in ROCE, further suggesting that STIM1 might be a universal regulator of Ca 2ϩ entry.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, impairment of this complex by shTRPC3 was without effect on TG-evoked SOCE. The role of STIM1 in non-capacitative receptor-regulated Ca 2ϩ entry pathways, such as Ca 2ϩ entry via arachidonate-regulated calcium (ARC) channels (59,60) has previously been demonstrated. Our results reporting the association of STIM1 with type I IP 3 R upon stimulation with ATP or CCh also shows the involvement of STIM1 in ROCE, further suggesting that STIM1 might be a universal regulator of Ca 2ϩ entry.…”
Section: Discussionmentioning
confidence: 99%
“…STIM1 is necessary for their activation, but only the fraction of STIM1 that is constitutively present in the PM (comprising about 10% -20% of the total STIM1 pool in most cells) (Mignen et al 2007). Concatemer studies suggest that ARC channels form as a pentamer of Orai subunits (3 Â Orai1 þ 2 Â Orai3), and glutamine substitutions for glutamates at E106 in Orai1 or the corresponding location in Orai3 (E81) both inhibit conductance, suggesting the formation of a pentameric glutamatergic selectivity filter (Mignen et al 2009).…”
Section: Arc Channelsmentioning
confidence: 99%
“…The unusually long coiled-coil domain of STIM1 likely provides the structural features needed for connection between the two membranes to transfer the signal from the ER to the PM that activates CRAC channel. A likely candidate for such interactions is PM-STIM1 (6,11,13,14). However, direct interactions with Orai1 are also possible.…”
Section: Analysis Of the Crac Channel Selectivity By Co-expression Ofmentioning
confidence: 99%
“…STIM1 functions as the Ca 2ϩ sensor in the ER that triggers the CRAC channel activation (5,6,11). However, its translocation to the PM upon activation (11,13) and functional role in the PM have also been demonstrated (6,14). Even though a report by Mignen et al (14) revealed that PM-STIM1 regulates another Ca 2ϩ channel (arachidonate-regulated Ca 2ϩ channels), the same group later revealed that arachidonate-regulated Ca 2ϩ channels have the same molecular identity as CRAC channels (Ref.…”
mentioning
confidence: 99%